Analisis Penggunaan E-learning Sebagai Media Pembelajaran Pada Peserta Didik Mata Pelajaran Sejarah Di Kelas XI D Sma Negeri 10 Pontianak : Penelitian - Lindaria Purba; Andang Firmansyah; Haris Firmansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This is the case study on the use of e-learning in history learning in Sma Negeri 10 Pontianak. The kind of research used in the method was a qualitative method with a descriptive approach. The research method used was qualitative, and the approach was descriptive. Collection techniques of data were done through observation, depth interviews, and documentation with students and teachers of history and school principals. The data analysis method followed the stages of data collection, reduction, presentation, and drawing conclusion. The results of this study are: 1) History learning planning prepared by teachers in class XI D SMA Negeri 10 Pontianak is done by preparing teaching modules, teaching materials, and learning media, as well as other learning support tools. Headlights (2) The use of e-learning to teach History subjects in class is not yet fully conducive to teachers carrying out learning. (3) Obstacles in using e-learning as a teaching medium in class. It can be concluded that the use of e-learning as a medium in teaching history in class. However this does not reduce students desire to learn, in fact students prefer learning using e-learning.